Site-Specific Variation in Familial Cancer as Suggested by Family History, Multiple Primary Cancer, Age at Onset, and Sex Ratio Associated With Upper, Middle, and Lower Third Esophageal and Gastric Cardia Carcinoma - Wen, Denggui; Wen, Junpeng; Zou, Wendi; Yang, Yi; Wen, Xiaoduo; Chen, Yuetong; Akazawa, Kohei; Geng, Cuizhi; Shan, Baoen (Frontiers in Oncology, 2020)
Background In China, esophageal squamous cell carcinoma (ESCC) and gastric cardia adenocarcinoma (GCA) differ in terms of multiple primary cancer (MPC) and male-to-female sex ratio (MFSR). Methods We studied site-specific variation in familial cancer by comparing family history (FH), MPC, age at onset (AO), and MFSR among 8768 patients with ESCC/GCA. Results ESCC/GCA patients with a positive FH are associated with a significantly higher rate of MPC and a younger AO than those without (sex-specifically: MPC 1.6% vs. 0.7%, P<0.01 and 3.2% vs. 0.8%, P<0.01; AO 53.1 ± 8.1 vs. 54.5 ± 8.2, P=0.000 and 52.9 ± 7.4 vs. 54.0 ± 8.0, P=0.005). Among patients with a positive FH, MPC decreases significantly from upper-, middle-, and lower-third ESCC to GCA (sex-specifically: 53.6%, 1.8%, 1.6%, 0.8%, P=0.000; and 71.4%, 1.5%, 2.2%, 1.6%, P=0.000). From MPC, upper-, middle-, and lower-third ESCC to GCA, AO increased sex-specifically: 51.9 ± 7.2, 52.8 ± 7.9, 52.1 ± 8.3, 54.3 ± 8.4, 55.6 ± 7.6 (P=0.000) and 49.3 ± 6.5, 51.8 ± 9.8, 52.6 ± 7.8, 54.4 ± 8.0, 55.7 ± 7.2 (P=0.000), and FH decreased: 43.8%, 35.1%, 28.2%, 29.5%, 24.4% (P=0.000) and 55.2%, 26.7%, 25.0%, 24.3%, 22.3% (P=0.000). The preponderance of males, smoking, alcohol consumption, and patients ≥50 years old increased from 2.2:1, 1.7:1, 1.0:1, 2.0:1 in ESCC to 6.1:1, 2.8:1, 2.5:1, 4.0:1 in GCA, yet more MPCs were associated with non-preponderant than preponderant counterparts; particularly in GCA, the difference was statistically significant. Conclusion The proportion of familial cancer may decrease from upper-, middle-, and lower-third ESCC to GCA. This entails molecular investigation, and appreciating this may help us devise a better screening strategy or individualize cancer treatment.